Nghiên cứu tổng hợp và tính chất xúc tác của zeolit ZSM-5 có tỉ số Si/Al khác nhau trong phản ứng cracking n-hexan - Hoài Nam, Lê Thị (Vietnam Journal of Chemistry, 2014)
ZSM-5 zeolites with different Si/Al ratios were successfully synthesized by hydrothermal treatment using template. The obtained samples were characterrized by different techniques such as X-ray diffraction (XRD), infrared resonance (IR) and scanning electron microscopy (SEM). The acidity of samples were determined by temperature programmed desorption amoniac method (TPD-NH3.). The activity of samples were tested on the cracking n-hexane. The results showed that the obtained ZSM-5 sample with a Si/Al ratio of 75 had the highest activity in the cracking n-hexane.